Ba'al and Seth : an investigation into the relationship of two gods, with reference to their iconography (ca. 1500 – 1000 BCE) - Cox, Michael James (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.